Pengaruh Model Problem Based Learning Terhadap Kemampuan Komunikasi Matematis Pada Materi Trigonometri Siswa Kelas X SMK IT Bolang - Silvia, Salu; Pratidiana, Deni (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
This research was motivated by the lack of variety in teaching carried out, as well as the low mathematical communication skills of students at SMK IT Bolang for the 2023/2024 academic year. This research aims to determine the effect of the problem based learning model on students mathematical communication skills. The method used in this research is quasi-experimental. The population in this study were students at SMK IT Bolang. The samples in this research were students in class X AP 1 as the experimental class and class X AP 2 as the control class. The instrument used by researchers was a test of students' mathematical communication skills with a total of 5 questions in the form of descriptions, where previously the questions had been tested for validity, reliability, difficulty index and distinguishing power and were tested first and the questions were declared suitable for use. The data analysis used is a test of the difference between two means, which previously carried out the prerequisites for normality and homogeneity tests. After the researchers conducted research using a learning model based on data exposure, researcher findings, and the discussion that has been described, it can be concluded that there is an influence of the problem based learning model on students' mathematical communication skills in the trigonometry material at SMK IT Bolang. In other words, students' mathematical communication skills among students who receive problem based learning are higher than students who receive conventional learning. Apart from that, it can be seen that student activity in the problem based learning model shows that students are active in learning both before and after learning.